indonesia Hubungan Pengetahuan Gizi dan Sikap Tentang Gizi Seimbang Dengan Praktik Diet Penurunan Berat Badan Pada Remaja Putri di SMA Dr. Soetomo Surabaya - Ningtyas, Pramitha Ayu (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Adolescence is a period in the human life span. Adolescence generally experiences a state of unrest caused by various kinds of changes both physical, psychologically and socially so that adolescents go on a weight loss diet. Weight loss diet practices will be successful if supported by an understanding of the right knowledge and attitudes. The purpose of this study was to determine the description of nutritional knowledge, attitudes with weight loss diet practices in adolescent girls at SMA Dr. Soetomo Surabaya and the relationship between nutritional knowledge and attitudes about balanced nutrition with weight loss diet practices in adolescent girls at SMA Dr. Soetomo Surabaya. The type of research used is correlational research using cross sectional research design. Respondents used in this study were 53 adolescent girls of SMA Dr. Soetomo Surabaya who met the inclusion and exclusion criteria. Data on balanced nutrition knowledge was taken using a test, attitude data was taken using a questionnaire while dietary practice data was taken using a statement questionnaire. Data analysis using statistical tests in the form of Pearson correlation. The results showed that there was a relationship between balanced nutrition knowledge and weightloss diet practices with a p value = 0.444 (p>0.05), while attitudes with weight loss diet practices had a relationship with a p value = 0.308 (p>0.05). Knowledge of balanced nutrition does not directly affect weight loss diet practices, while attitudes directly affect weight loss diet practices.Keywords: Nutrition Knowledge, Attitude, Adolescent Girls and Weight Loss Diet Practices